2008
DOI: 10.3844/ajessp.2008.608.614
|View full text |Cite
|
Sign up to set email alerts
|

Review of Malaysian Agricultural Policies with Regards to Sustainability

Abstract: Abstract:The new scientific knowledge coupled with concerns for the environmental, economic and social aspects of agriculture brought Malaysian agriculture into a state of transition. The need for reviewing Malaysian agricultural policies has arisen due to that fact that current agricultural practices in the country are found to be related to environmental, economic and social problems. This study is an effort to review the current Malaysian agricultural policies with regards to sustainability. The Third Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 1 publication
2
24
0
Order By: Relevance
“…In the Third National Agriculture Policy (NAP3), organic agriculture was identified as a niche market opportunity for Malaysian small-scale producers (Ahmad, 2001). Even though the national agricultural policies are along with the standard of sustainable agriculture, but the current agricultural practices differ in terms of sustainability (Murad, Mustapha, & Siwar, 2008) and efforts made to promote OF in Malaysia have not generated acceptable results. A number of farmers have also been adopted sustainable agriculture in general and OF in particular practices are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In the Third National Agriculture Policy (NAP3), organic agriculture was identified as a niche market opportunity for Malaysian small-scale producers (Ahmad, 2001). Even though the national agricultural policies are along with the standard of sustainable agriculture, but the current agricultural practices differ in terms of sustainability (Murad, Mustapha, & Siwar, 2008) and efforts made to promote OF in Malaysia have not generated acceptable results. A number of farmers have also been adopted sustainable agriculture in general and OF in particular practices are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…From the study, it has been shown that using Information and Communication Technology (ICT) tools in the learning environment can be used to educate and promote sustainable practices to the public. However, other factors such as good perceptions (Bagheri et al, 2008), interactive and cooperation between farmer, government, research institution and policy-maker are important factor in achieving sustainable agriculture (Murad et al, 2008;Sharghi et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Mustapha and Jani (1995) also state, awareness among society about environmental pollution and resources extinct can help Malaysia to develop sustainable agriculture. More intensive monitoring and investigating the agricultural practices would enable Malaysia to achieve sustainability (Murad et al, 2008). As a solution, introducing the use of virtual technology through learning as a tool to promote sustainable awareness in paddy farming practices in order to increase public awareness is among the best alternatives available.…”
Section: Creating Awareness In Sustainable Agriculturementioning
confidence: 99%
“…The increase in social and environmental ills resulting from the encroachment by businesses is enough justification by itself (Bataineh, 2006). The non-conventional elements of SEA and its adherence to noble values that are compounded with religious undertones are essential for the accounting students and the practitioners in order to confront organization's agenda towards the society and the environment and ultimately the sustainability issue (Burritt and Schltegger, 2010;Murad et al, 2008). The results of the study indicate that accounting educators in Malaysia are receptive towards the idea of SEA accounting education as a means towards confronting the social and environmental problems which in part could be due to unethical business and accounting practices.…”
Section: Discussionmentioning
confidence: 99%